Magnetic resonance elastography (MRE) for measurement of muscle stiffness of the shoulder: feasibility with a 3 T MRI system. (September 2016) - Hong, Sun Hwa; Hong, Suk-Joo; Yoon, Joon-Shik; Oh, Chang-Hyun; Cha, Jang Gyu; Kim, Hee Kyung; Bolster, Bradley
Background: Magnetic resonance elastography (MRE) at 3 T MR has the potential to improve the objective detection of skeletal muscle stiffness. Purpose: To determine the feasibility of MRE using 3 T MR for measurement of the stiffness of shoulder muscles in subjects. Material and Methods: This study prospectively evaluated 16 healthy subjects (mean age, 29.8 years; range, 25–51 years). MRE was acquired with 3 T MR through the use of a 2D-gradient-echo-based MRE sequence at two different excitation frequencies (90 and 120 Hz). The mean stiffness values (MSV) of the trapezius and infraspinatus muscles were measured by two radiologists. Differences between the MSV in the x, y, and z motion-sensitization directions were assessed. Inter-observer agreement was also measured. Results: The MSV of the trapezius muscle were 2.72 kPa ± 0.6 (SD) at 90 Hz and 4.66 kPa ± 1.2 at 120 Hz, while the MSV for the infraspinatus muscle were 3.2 kPa ± 0.52 at 90 Hz and 4.38 kPa ± 0.92 at 120 Hz. The MSV for both muscles were significantly higher at 120 Hz than at 90 Hz ( P  < 0.05). The MSV in the three different directions were significantly different from each other in the infraspinatus muscle ( P  < 0.05). Levels of inter-observer agreement regarding MSV were good to excellent for both the trapezius (intraclass correlation coefficient [ICC] = 0.979–0.996) and infraspinatus muscles (ICC = 0.614–0.943). Conclusion: MRE at 3 T is a feasible technique for the evaluation of shoulder muscle stiffness. Extended application of skeletal muscle MRE at 3 T will contribute to the evaluation and treatment of skeletal muscle disorders.